Cognitive Factors and Residual Speech Errors: Basic Science, Translational Research, and Some Clinical Frameworks - Eaton, Catherine Torrington (Seminars in Speech and Language, 2015)
This article explores the theoretical and empirical relationships between cognitive factors and residual speech errors (RSEs). Definitions of relevant cognitive domains are provided, as well as examples of formal and informal tasks that may be appropriate in assessment. Although studies to date have been limited in number and scope, basic research suggests that cognitive flexibility, short- and long-term memory, and self-monitoring may be areas of weakness in this population. Preliminary evidence has not supported a relationship between inhibitory control, attention, and RSEs; however, further studies that control variables such as language ability and temperament are warranted. Previous translational research has examined the effects of self-monitoring training on residual speech errors. Although results have been mixed, some findings suggest that children with RSEs may benefit from the inclusion of this training. The article closes with a discussion of clinical frameworks that target cognitive skills, including self-monitoring and attention, as a means of facilitating speech sound change.
Keywords: Cognitive factors; residual speech errors; executive functions; memory; attention; self-monitoring